Development of Maize Hybrids With Enhanced Vitamin-E, Vitamin-A, Lysine, and Tryptophan Through Molecular Breeding - Das, Abhijit K.; Gowda, Munegowda M.; Muthusamy, Vignesh; Zunjare, Rajkumar U.; Chauhan, Hema S.; Baveja, Aanchal; Bhatt, Vinay; Chand, Gulab; Bhat, Jayant S.; Guleria, Satish K.; Saha, Supradip; Gupta, Hari S.; et al. (Frontiers in Plant Science, 2021)
Malnutrition is a widespread problem that affects human health, society, and the economy. Traditional maize that serves as an important source of human nutrition is deficient in vitamin-E, vitamin-A, lysine, and tryptophan. Here, favorable alleles of vte4 (α-tocopherol methyl transferase), crtRB1 (β-carotene hydroxylase), lcyE (lycopene ε-cyclase), and o2 (opaque2) genes were combined in parental lines of four popular hybrids using marker-assisted selection (MAS). BC1F1, BC2F1, and BC2F2 populations were genotyped using gene-based markers of vte4, crtRB1, lcyE, and o2. Background selection using 81–103 simple sequence repeats (SSRs) markers led to the recovery of recurrent parent genome (RPG) up to 95.45%. Alpha (α)-tocopherol was significantly enhanced among introgressed progenies (16.13 μg/g) as compared to original inbreds (7.90 μg/g). Provitamin-A (proA) (10.42 μg/g), lysine (0.352%), and tryptophan (0.086%) were also high in the introgressed progenies. The reconstituted hybrids showed a 2-fold enhancement in α-tocopherol (16.83 μg/g) over original hybrids (8.06 μg/g). Improved hybrids also possessed high proA (11.48 μg/g), lysine (0.367%), and tryptophan (0.084%) when compared with traditional hybrids. The reconstituted hybrids recorded the mean grain yield of 8,066 kg/ha, which was at par with original hybrids (mean: 7,846 kg/ha). The MAS-derived genotypes resembled their corresponding original hybrids for the majority of agronomic and yield-related traits, besides characteristics related to distinctness, uniformity, and stability (DUS). This is the first report for the development of maize with enhanced vitamin-E, vitamin-A, lysine, and tryptophan.